Qualitative Measure of the Degree of Internationalization: The Case of Huawei - López Morales, José Satsumi (México y la Cuenca del Pacífico, 2021)
The study of the “degree of internationalization” (DOI) is an important topic in the academic literature of international business. Therefore, the main objective of this work is to measure the DOI of the Chinese company, Huawei, from the perspective of the “depth” and “breadth” of the DOI. To achieve this objective, a qualitative content analysis technique was utilized to analyze Huawei Company’s annual reports over 14-year, from 2006 to 2019, to extract the frequency of words associated with the DOI to carry out the measurement. Huawei’s annual reports for this period were collected from the company’s institutional page. The primary results obtained indicate an increase in the DOI for Huawei in the two dimensions studied of depth and breadth. Also, these results indicate a trend similar to the number of employees and Huawei earnings in the period from 2006 to 2019.